Pengaruh Fear of Missing Out dan Price Discount terhadap Tingkat Impulsif Buying Product Skintific di Tiktok Shop (Studi Kasus di Kelurahan Tanjung Rejo, Medan Sunggal, Kota Medan) - Kartiwi, Putri Sri; Nasution, Amrin Mulia Utama (Mahesa Research Center, 2025)
This study aims to find out and analyze the influence of Fear Of Missing Out and Price Discount on the level of Impulse Buying of Skintific products on Tiktok Shop (Case Study in Tanjung Rejo Village, Medan Sunggal, Medan City). FOMO is the fear of missing out on trends that encourages impulse purchases, while Price Discount is a marketing strategy that increases the appeal of a product. The research method used was quantitative, with 100 respondents selected using Purposive Sampling, namely active TikTok Shop users who had purchased Skintific products. Data analysis was carried out by multiple linear regression. The results of the study showed that Fear Of Missing Out had a significant effect on Impulse Buying, this can be seen from the significant value (0.009) of 0.05 and the tcount (2.686) compared to the table (1,984). Price Discount has a significant effect on Impulse Buying, this can be seen from the significant value (0.000) from 0.05 and tcount (6.679) compared to ttable (1,984). Fear Of Missing Out (X1) and Price Discount (X2) are simultaneously significant to Impulsive Buying (Y), this can be seen from the value of FcalFtabel and its significance level (0.000) 0.05.